2016
DOI: 10.1038/srep38248
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and transcriptomic analysis of a novel marine strain Bacillus weihaiensis reveals the mechanism of brown algae degradation

Abstract: A novel marine strain representing efficient degradation ability toward brown algae was isolated, identified, and assigned to Bacillus weihaiensis Alg07. The alga-associated marine bacteria promote the nutrient cycle and perform important functions in the marine ecosystem. The de novo sequencing of the B. weihaiensis Alg07 genome was carried out. Results of gene annotation and carbohydrate-active enzyme analysis showed that the strain harbored enzymes that can completely degrade alginate and laminarin, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…These adaptations match those of pivotal polysaccharide degraders such as Zobellia galactanivorans [31], substantiating the relevance of A. macleodii for the remineralization of algal polysaccharides [33,34]. The prioritization of laminarin over alginate was diametric to Bacillus weihaiensis [30], possibly indicative of different ecological niches. B. weihaiensis has been isolated from macroalgae and hence regularly encounters alginate from cell walls, whereas A. macleodii is rarely found on macrophytes and may primarily target storage laminarin released by exudation or decay.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These adaptations match those of pivotal polysaccharide degraders such as Zobellia galactanivorans [31], substantiating the relevance of A. macleodii for the remineralization of algal polysaccharides [33,34]. The prioritization of laminarin over alginate was diametric to Bacillus weihaiensis [30], possibly indicative of different ecological niches. B. weihaiensis has been isolated from macroalgae and hence regularly encounters alginate from cell walls, whereas A. macleodii is rarely found on macrophytes and may primarily target storage laminarin released by exudation or decay.…”
Section: Resultssupporting
confidence: 52%
“…We hypothesize that the structuring influence of marine polysaccharide mixtures on bacterial dynamics resembles processes among human gut microbiota, including sequential substrate utilization through catabolite repression and regulatory networks [25][26][27], with ecological implications on cellular and community levels [28,29]. Indeed, a recent study in marine systems revealed that sequential degradation of alginate and laminarin in Bacillus coincides with temporal regulation of the respective PUL [30]. The ecological relevance of such adaptations is highlighted by substrate-controlled regulation of hydrolytic machineries for brown/green/red algae polysaccharides in Zobellia galactanivorans [31] and sophisticated laminarin uptake systems [32].…”
Section: Introductionmentioning
confidence: 99%
“…And NHE is regularly cited as a candidate because of its cytotoxic, necrotic and haemolytic activities on human intestinal cell lines (Lindback et al 2004; Zhu et al 2016). Some B. cereus genomes harbor the nhe operon which codes for the cytolytic protein NheA and the binding components NheB and NheC (Wehrle et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicated a tight and speciesspecific association of Z. galactanivorans to macroalgae. Similarly, Bacillus weihaiensis, a brown-algae-associated Firmicutes, produces enzymes that enable the complete degradation of alginate and laminarin, which are major components of brown algae polysaccharides (Zhu et al, 2016). In this case, the same heterotrophic bacterium was responsible for a succession of degradation processes: First, alginate was degraded and thus the cell wall destructed, and subsequently the released laminarin and mannitol utilized (Zhu et al, 2016).…”
Section: Effects Of Algal Exopolysaccharide Release On the Metabolismmentioning
confidence: 99%
“…Similarly, Bacillus weihaiensis, a brown-algae-associated Firmicutes, produces enzymes that enable the complete degradation of alginate and laminarin, which are major components of brown algae polysaccharides (Zhu et al, 2016). In this case, the same heterotrophic bacterium was responsible for a succession of degradation processes: First, alginate was degraded and thus the cell wall destructed, and subsequently the released laminarin and mannitol utilized (Zhu et al, 2016). These, at a first glance, contradictory observations of low and high substrate specificity can be explained by different bacterial lifestyles, and thus associations of copiotroph and oligotroph bacterial species to phytoplankton.…”
Section: Effects Of Algal Exopolysaccharide Release On the Metabolismmentioning
confidence: 99%